Diagnostic evaluation of myeloperoxidase and Cardiac Troponin I in patients with acute coronary syndrome - Riaz, Muhammad (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the diagnostic accuracy of myeloperoxidase and cardiac troponin-I in patients with acute coronary syndrome. Method: The validity study was conducted from January to November 2018 at the Emergency and Pathology departments of the Punjab Institute of Cardiology, Lahore, and the Department of Pathology, Postgraduate Medical Institute, Lahore, Pakistan, and comprised adult patients of either gender who presented with complaint of constrictive pericarditis for testing the myeloperoxidase MPO and cardiac troponin-I concentrations. Data was obtained related to age, gender and electrocardiogram, and sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy were determined. Data was analysed using SPSS 20. Results: Of the 62 patients with mean age 56.40+11.39 years, 49(79%) were males, 15(42%) were aged 51-60 years, 24(38.7%) had ST elevation, and 21(33.9%) had normal electrocardiogram. For myeloperoxidase, there were 13(21%) true positive, 39(63%) false negative and 10(16%) true negative cases. For cardiac troponin-I, there were 52(84%) true positive and 10(16%) true negative cases. The sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy values were 25%, 100%, 100%, 20.4% and 37%, respectively. Conclusion: Early prognostic assessment is necessary for application of proper treatment and management. Key Words: Diagnosis, Myeloperoxidase, Cardiac troponin-I, Acute coronary syndrome.